2008
DOI: 10.1002/jmri.21531
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted MR imaging for the evaluation of seminal vesicle invasion in prostate cancer: Initial results

Abstract: Purpose:To evaluate the accuracy of T2-weighted (T2WI) with diffusion-weighted imaging (DWI) as compared with T2WI alone for predicting seminal vesicle invasion (SVI) of prostate cancer. Materials and Methods:A total of 30 patients with SVI and 136 patients without SVI who underwent prostate MR imaging were included in the study. MR images were analyzed retrospectively and independently by two readers for SVI on T2WI and T2WI with DWI using a 5-point scale.Results: For predicting SVI, the specificity for T2WI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…We found that mean Most of the studies to date that have assessed the utility of DWI in PCa evaluated lesions within the peripheral zone (PZ). Several studies (41)(42)(43)(44) have suggested improvement in tumor detection over T2W, either using DWI alone, or in combination with T2W. Results for comparison between DWI and MRS have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mean Most of the studies to date that have assessed the utility of DWI in PCa evaluated lesions within the peripheral zone (PZ). Several studies (41)(42)(43)(44) have suggested improvement in tumor detection over T2W, either using DWI alone, or in combination with T2W. Results for comparison between DWI and MRS have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al [16] showed that the sensitivity and specificity rates for T2WI was 76% and 70% respectively, compared with 86% and 80% for DWI. Combined T2WI and DWI yield slightly better results, with reported sensitivity and specificity rates of 45-89% and 61-97% respectively, compared with 74-85% and 57-95% respectively for DWI alone and 25-87% and 57-92% respectively for T2WI alone [12,15,[17][18][19][20][21][22][23][24][25][26].…”
Section: Potential Uses Of Dwi In Prostate Cancer Detectionmentioning
confidence: 94%
“…Ren and colleagues [23] showed that the combined use of DWI with T2WI is superior to T2WI alone for detecting SVI, while noting that ADC values are lower in PC than in normal seminal vesicles. Kim et al showed increased specificity (87% to 97%) and accuracy (87% to 96%) for SVI by combining DWI and T2WI compared with T2WI alone; substantial inter-reader agreement was found despite the presence of haemorrhage within the SV in a number of patients [18]. Interestingly, the increase in accuracy and specificity was greater for the less experienced reader.…”
Section: Extraprostatic Involvementmentioning
confidence: 98%
See 1 more Smart Citation
“…In a separate study, Kim et al assessed 30 patients with PCa and SVI using T2 and DW imaging on a 3-Tesla magnet. 21 The addition of sequenced imaging significantly improved SVI detection, particularly for the less experienced radiologist. However, this group did not utilize DCE, and neither study validated the findings with preoperative biopsy.…”
Section: Discussionmentioning
confidence: 99%